Infrastructure endowment and investment as determinants of regional growth in the European Union - Riccardo Crescenzi; Andrés Rodríguez-Pose (EIB Papers, 2008)
This paper analyses the role of infrastructure endowment and investment in the genesis of regional growth in the European Union. It assesses the economic effects of the existence and improvement of transport networks in light of their interactions with innovation and local socio-economic conditions. The analysis accounts for spatial interactions between different regions in the form of spillovers and network externalities. The regression results highlight the impact of infrastructural endowment on regional economic performance, but also the weak contribution of additional investment. Regions having good transport infrastructure endowment and being well connected to regions with similar good endowments tend to grow faster. However, investment in infrastructure within a region or in neighbouring regions seems to leave especially peripheral regions more vulnerable to competition. Furthermore, the positive impact of infrastructure endowment on growth tends to wane quickly and is weaker than that of, for example, the level of human capital
Keywords: 330; Verkehrsinfrastruktur; Verkehrsinvestition; Regionales Wachstum; EU-Staaten